Analisis Efektivitas Penggunaan Sistem Informasi Akuntansi (Aplikasi Passion) Terhadap Produk Gadai KCA Pada PT. Pegadaian Persero Cabang Nagoya - Dilla Dwi Rahmatin Rusfa; Seri Apri (Journal of Applied Accounting And Business, 2022)
This research aims to find out the Effectiveness of Accounting Information System for KCA Pawn Services at PT. Pegadaian Persero Nagoya Branch. This research uses a quantitative descriptive method. With data collection techniques in the form of primary and secondary, by means of observation, interview, and documentation. The results of this research show that the accounting information system is applied by PT. Pegadaian Pesero Nagoya Branch has been running effectively as seen from several components to support the intelligence of the information system, namely related parts (HR), documents used, accounting records used, loan dispossession procedures provided and rent modal at pawnshops. Admission procedures from transfers at pawnshops, lelang admission and sales procedures on pawnshops as well as turnover income from KCA pawns.